Specific Features of the Legal Status of the Ili Province between 1760 and the 1860s - Pochekaev, Roman Yu (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2018)
The author makes an attempt at analysing the legal status of the Ili Province, the region of the Qing Empire which had been an independent Junghar Khanate conquered by the Manchu dynasty at the turn of the 1760s. Referring to different sources and research works, the author characterises the legal status of the Ili Province from its foundation in the early 1760s to the Muslim rebellion of the early 1860s which resulted in the region’s separation from the Qing Empire. The author analyses the administrative system and the local government, the status of specific groups of population, the policy of Qing regional authorities as regarded foreigners (subjects of Central Asian khanates and the Russian Empire), and its regulations in the field of trade and taxation. The author refers to a wide range of notes of Russian diplomats and merchants who visited the Ili Province between 1770 and the 1860s which makes the work innovative. The analysis of these materials allows the author to describe the formally fixed legal status of the region, its population and foreigners but also the specific features of putting legal regulations into practice, and problems which the Manchu authorities faced in the Ili Province connected with the population and subjects of the neighbouring states. The author concludes that the Ili Province in 1760–1860s had a “transitional character” which caused a specific legal status both Manchu subjects and foreigners had, and which was different from their status in other Chinese regions. Later, this specific status was fixed legally, specifically in the Russian-Chinese treaties on the rights of Russian subjects in the Ili Province.